Public opinion on the sentencing of mentally ill female offenders; factors that influence people's perceptions of appropriate punishments and the impact of personal experience on sentencing judgements - Adams, Claire (2010)
The aim of the current study was to explore public opinion on mentally ill female offenders in Western Australia, and the influence of these views on sentencing decisions. This study aimed to determine whether the mental health of a female offender influenced how people view a crime and the punishment they consider most appropriate for an offender. In addition, it aimed to investigate whether knowing someone with a mental illness influences people's perception of a crime and the sentencing decisions favoured for a mentally ill female offender. The study involved a between-subjects design comprising 118 participants, who received one version of a scenario depicting a female offender who was either mentally ill or whose mental health was not mentioned. Participants were asked to rate the seriousness of the offence, the offender's responsibility for their crime, the severity of punishment which should be imposed and the purpose of punishment most appropriate for the offender. In addition a qualitative component was included to help determine the reasoning behind people's quantitative decisions. Results indicated that people are significantly more lenient in their view of a crime and sentencing decisions when a female offender is known to have a mental illness. No significant differences were found in regards to the preferred purpose of punishment however, with rehabilitation selected as the favoured goal of punishment regardless of the offender's mental health. In addition knowing someone with a mental illness was not found to significantly impact people's perception of a crime or the sentencing decisions preferred for a mentally ill female offender. Future research is required to obtain a representative sample of the West Australian population in order to enhance the external validity of these findings